The influence of financial attitudes, locus of control, education on financial management behavior with financial literacy as a moderating variable - Hutapea, Herti Diana; Manurung, Amran; Sitompul, Andreas Sebatian (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of financial attitudes, locus of control, education on financial management behavior with financial literacy as a moderating variable in MSMEs in Medan City, North Sumatra. Data collection using questionnaire distribution. The sampling technique used in this study was accidental random sampling technique. The sample to be used in this study was 100 MSME business actors in Medan city who were assisted by the Cooperative and UKM office of North Sumatra province. The results showed that financial attitudes and locus of control had a positive and significant effect on the financial management behavior of MSMEs in Medan city while education had a negative and insignificant effect on the financial management behavior of MSMEs in Medan city. Furthermore, financial literacy does not moderate the relationship between financial attitudes, locus of control and education on the financial management behavior of MSMEs in Medan City, North Sumatra. Because the results of this study indicate the absence of a moderating relationship, the moderating variable in this model is thought to have a direct effect because the effect of financial literacy on financial management behavior shows because the calculated T value is 3.034> 1.96 and the P value is 0.001 <0.05 so that researchers propose to use mediating variables for further research.